Горячий снег - Бондарев Юрий Васильевич (Советский писатель, 1985)
Экземпляры: Селтинская районная библиотека (к/х) (20211112) / Инвентарный номер: 102915 / Цена: / Авт.знак: Б81 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6